ANALISIS KOMPETENSI DOSEN PENGAMPU MATA KULIAH MANAJEMEN KEUANGAN LANJUTAN DARI PERSEPSI MAHASISWA PRODI S-1 MANAJEMEN SEMESTER 4D, 4E, 4G DAN 4H STIE BALIKPAPAN - Rudy Pudjut Harianto (Jurnal GeoEkonomi, 2020)
This research aims to analyze the competence of lecture of advanced financial management lesson from college student perceptions of management study programs at STIE Balikpapan. Data Analysis Methods used in this research are validity, reliability, and descriptive statistical analysis. The sample of the research is S-1 of management study program Semester IVD, IVE, IVG and IVH. The validity test results are known that the calculated r value of each statement item tested is greater than the value of r table. Therefore, all statement items on each variable are declared valid and can be used as data collection tools. The reliability test results can be concluded that the variables Pedagogical Competence, Professional Competence, Personality Competence, and Social Competence show the Alpha coefficient value greater than 0.60. So that all variables in the research are declared reliable and can be used as a data collection tool. College student perceptions of lecturer competencies: (1) Pedagogical Competence shows the highest respondents' answers with good criteria, namely 55 people (52%); (2) Professional Competence shows the highest respondent's answer with good criteria, namely 54 people (51%); (3) Personality Competence shows the highest respondent's answer with good criteria that is 54 people (51%); (4) and Social Competence shows the highest respondents' answers with good criteria as many as 50 people (47%).